Burglary victimization in England and Wales, the United States andThe Netherlands - Tseloni, Andromachi; Wittebrood, Karin A.; Farrell, Graham; Pease, Ken (The British journal of criminology, 2004)
This study examines factors relating to burglary incidence in England and Wales, the United States, and the Netherlands. Negative binomial regression models are developed based on routine activities theory. Data are drawn from national victimization surveys of about the same time: the 1994 British Crime Survey, the 1994 National Crime Victimisation Survey, and the 1993 Police Monitor, respectively. Relative to the two European countries, US households have more idiosyncratic patterns of burglary victimization. Despite differences across the three data sets, several similar effects emerge of variables tapping lifestyle characteristics on burglary victimization. Four variables had significant effects in the same direction in two or more countries where the third country showed a non-significant effect in the same direction. These were age, lone parent household status, urbanization, and the presence of security measures in the home. Some variables had significant effects in opposite directions according to country: rented accommodation was associated with higher burglary rates in the UK but lower rates in the Netherlands; household affluence was linked with higher rates of burglary in the UK and lower rates in the United States